Effect of Rehabilitation Training based on Mirror Vision Feedback on the Old Age Stroke Patients with Hemiplegia - Bo GENG; Hanchao FENG; Jian ZHANG; Xiaoxue WANG (康复学报)
Objective:To observe the effect of rehabilitation training based on mirror vision feedback on upper and lower limb muscle strength, motor function and quality of life in old age stroke patients with hemiplegia.Methods:A total of 120 old age stroke patients with hemiplegia were treated in the outpatient department and inpatient department of Rehabilitation Department of the First Affiliated Hospital of Harbin Medical University from March 2017 to March 2019. The patients were randomly divided into the control group and the observation group, with 60 cases in each group, according to the method of random number table. The control group was given routine rehabilitation training including hemiplegic side limb exercise (5-10 times for each item, and 2-3 cycles every day), standing balance (30 min a time, one time a day), sitting balance (30 min a time, one time a day), walking (30 min a time,2-3 times per day), daily activities (30 min a time,2-3 times every day), treatments for five days per week and continuous treatment for four weeks. The observation group was given rehabilitation training based on mirror vision feedback, under the guidance of professional doctors. The patients focused on observing their own mirror image of motion imaging, imagining the seen motion imaging as their own patient side and making the patient side complete the training independently as much as possible. The training contents were the same as that of the control group, treatments for five days per week, continuous treatment for four weeks. The muscle strength of upper and lower extremities was assessed by the modified Ashworth muscle tension scale (MAS), the motor function of upper and lower extremities was assessed by Fugl-Meyer motor function score (FMA), and the quality of life was assessed by activity of daily living scale (ADL).Results:Before treatment, there was no significant difference in the scores of muscle strength, motor function and quality of life between the two groups (P>0.05). Compared with before treatment, the MAS scores of upper limb (pronator and elbow flexors of the affected side) and lower limb (flexion and extensor groups of the affected hip) in the two groups were significantly lower at 4 weeks after treatment, and the difference was statistically significant (P<0.05), while the FMA scores and ADL scores of upper limbs and lower limbs in the two groups were significantly higher at 2 and 4 weeks after treatment, and the difference was statistically significant (P<0.05). Compared with the control group, the MAS scores of upper and lower limbs in the observation group were significantly lower at 4 weeks after treatment, and the difference was statistically significant (P<0.05); the FMA and ADL scores of upper limbs and lower limbs in the observation group were significantly higher at 2 and 4 weeks after treatment, and the difference was statistically significant (P<0.05).Conclusions:The rehabilitation training based on mirror vision feedback can improve the muscle strength of upper and lower limbs and the motor function of elderly stroke patients with hemiplegia, and it can improve the quality of life of patients, it's worthy of further clinical promotion.